Palm-based liquid crystals containing schiff base ester linking group: Synthesis and structure-mesomorphic properties / Lee Weng Nam - Lee , Weng Nam (2023)
In the present study, one of the five basic building blocks of oleochemicals, palm fatty acid, was chosen as flexible moiety in the synthesis of liquid crystals (LCs) due to its good reactivity for chemical modifications and non-toxicity. Three new series of palm-based liquid crystals (PBLCs), namely, PB1 – PB3, PB4 – PB6 and PB7 – PB9 consisting of Schiff base ester-based mesogenic core have been successfully synthesized. The chemical structure of all synthesized PBLCs was characterized and confirmed by Fourier Transform Infrared Spectroscopy (FT-IR), 1H and 13C Nuclear Magnetic Resonance (NMR). Polarizing Optical Microscopy (POM) revealed that the synthesized PBLCs were monomorphic and enantiotropic in nature exhibiting only smectic A phase upon heating and cooling except for PB9 in which smectic A phase can only be seen in the cooling cycle (monotropic). The phase transition temperatures observed under POM were found to be in good agreement with the Differential Scanning Calorimetry (DSC) thermograms obtained. The mesophase texture of smectic A phase was further verified by Small Angle X-ray Scattering (SAXS). The presence of a three-ring Schiff base ester-based mesogeniccore with a terminal bromo group within the series of PB1 – PB3 has led to higher molecular linearity and polarizability which eventually resulted in a stable mesophase range. As for the unsubstituted analogues of PB4 – PB6 series, the mesophase range was found to be narrower due to lower molecular polarizability with the absence of bromo group as terminal substituent. PB7 – PB9 series is composed of a mesogenic core with one less phenyl ring and an ester group. Therefore, owing to its lower molecular linearity and polarizability, PB7 – PB9 exhibited the least stable smectic A phase. As far as thermal stability is concerned, all synthesized PBLCs were found to be thermally stable above 300oC except for PB3 (decomposed with 5% weight loss at 281.66oC), PB4 and PB5 (decomposed with 5% weight loss at 201oC).